Geologia e paleontologia do biohermito da Formação Pirabas (Mioceno Inferior) - TÁVORA, Vladimir de Araújo (2015)
This work concerns with the detailed geological and paleontological study of the reef facies of the Pirabas Formation, that outcrop at the Maçarico beach, of Salinópolis district, Pará State, as a small, isolated and lenticular sedimentary bodie developed in the inner platform inner ramp of the Pirabas Sea. The biotic constituents are diverse and composed by three groups of coralline algae, sponges, corals, bryozoans, echinoids, foraminifera, ostracodes and molluscs. Three stages of the ecologic sucession were recognized in this patch reef: stabilization, colonization and diversification. Thin micritic crusts, recognized at top of the beds in diversification stage suggest the degradation of the environmental conditions favorable to reef accretion probably due to continentalization of the depositional site. The petrographic investigation reveals only one, homogeneous depositional microfacies, named biomicrite, without compositional and textural changes. The marine cementation is represented by microcrystalline agglomerates and micritic cement, locally neomorphosed to biosparite and detrital carbonatic components of the unconsolidated biogenic debris, resulted from the disintegration of the aragonite from the algalic remains accumulated as micritic mud. In the construction of the reef framework the red macroalgae were fundamental to the lithification and building of the framework, and very important to the protection and cementation of the others constituents.